Wizualizacja obiektów symbolicznych - Gliwa, Małgorzata (Visualization of Symbolic Objects, 2009)
In the article, Zoom Star technique is presented, which allows for graphical representation of symbolic objects. 2D and 3D graphs were used. Next, classification of symbolic objects taken from real database was carried out. The hierarchical agglomerative method for symbolic objects was used. Results were presented both in the form of dendrogram and 2D and 3D graphs. On the basis of these graphs a comparative analysis of classes was done. Calculations were made in the programme SODAS and R.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 143-152